2017
DOI: 10.1038/tp.2017.144
|View full text |Cite
|
Sign up to set email alerts
|

Altered neurite morphology and cholinergic function of induced pluripotent stem cell-derived neurons from a patient with Kleefstra syndrome and autism

Abstract: The aim of the present study was to establish an in vitro Kleefstra syndrome (KS) disease model using the human induced pluripotent stem cell (hiPSC) technology. Previously, an autism spectrum disorder (ASD) patient with Kleefstra syndrome (KS-ASD) carrying a deleterious premature termination codon mutation in the EHMT1 gene was identified. Patient specific hiPSCs generated from peripheral blood mononuclear cells of the KS-ASD patient were differentiated into post-mitotic cortical neurons. Lower levels of EHMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 73 publications
1
30
0
2
Order By: Relevance
“…Both accelerated and decreased neurite outgrowth have also been implicated as important neurodevelopmental cellautonomous phenotypes in ASD and SZ. In an iPSC-based model of Kleefstra-syndrome, a syndromic and genetically well described subtype of ASD, NPCs demonstrated increased proliferation, while neurite arborization was reduced in mature neurons (45). It has also been shown that KHSRP regulates the mRNA-stability of GAP43, an important player in the process of axonal and dendritic growth (46).…”
Section: Discussionmentioning
confidence: 99%
“…Both accelerated and decreased neurite outgrowth have also been implicated as important neurodevelopmental cellautonomous phenotypes in ASD and SZ. In an iPSC-based model of Kleefstra-syndrome, a syndromic and genetically well described subtype of ASD, NPCs demonstrated increased proliferation, while neurite arborization was reduced in mature neurons (45). It has also been shown that KHSRP regulates the mRNA-stability of GAP43, an important player in the process of axonal and dendritic growth (46).…”
Section: Discussionmentioning
confidence: 99%
“…Many genes in this pathway are involved in the pathogenesis of many psychiatric disorders, such as ASD (Wen et al 2016), attention deficit and hyperactivity disorder (ADHD), bipolar disorder, and schizophrenia (Zhao et al 2018). Moreover, the protein encoded by MAPK7 is a member of the MAPK family involved in a wide variety of cellular processes, such as proliferation, differentiation, transcription regulation, and brain development (Pearson et al 2001), and abnormalities in these processes can lead to the development of ASD symptoms (Nagy et al 2017;Courchesne et al 2019). Previous evidence also indicated rare mutations in the MAPK gene family participating in ASD, such as MAPK3 (Park et al 2017) and MAPK1 knockout mice showing ASD-like behavior (Satoh et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The method of disease modeling with patient-specific iPSCs can be applied to all types of chromosomal inherited diseases, from monogenetic to complex polygenetic disorders [25][26][27][28]. iPSCs hold great promise for disease modeling and regenerative therapies.…”
Section: Discussionmentioning
confidence: 99%